Rancang Bangun Sistem Informasi Administrasi Penjualan (Studi Kasus: Pada Toko Baria): Rancang Bangun Sistem Informasi Administrasi Penjualan (Studi Kasus: Pada Toko Baria) - Rizki, Rizki Ridwan; Faisal, Achmad; Reza Alpha Pahlevi, Ahmad (Fakultas Teknik Universitas Ibnu Sina, 2024)
The Sales Administration Information System in Stores is a system designed to simplify the sales administration process. This system aims to increase efficiency and accuracy in recording and managing sales data, as well as providing easy access to the information needed for shop owners and their staff. The implementation of the Sales Administration Information System in Stores is expected to increase store productivity and service quality, as well as assist in making strategic decisions to increase profitability and overall business growth.